Surgical Treatment of Lung Abscess Due to an Awn Aspiration in a 9-Year-Old Child: A Case Report - Angelina Vlahova; Zdravka Antonova; Edmond Rangelov; Nikola Kartulev; Velichka Oparanova; Natalia Gabrovska; Albena Spasova; Svetlana Velizarova; Hristo Shivachev (Children, 2023)
Introduction: Foreign body aspiration is a common condition in the child population and is one of the leading causes of accidental deaths in children. The aspiration of an awn (grass inflorescences) is extremely rare. Aim of the study: This study aims to describe the symptoms, diagnosis, therapeutic difficulties, and results of the aspiration of grass inflorescence. They are all related to the shape of the awn’s head and its behavior in the tracheobronchial tree. Case description: We present a 9-year-old boy with a history of an awn aspiration and recurrent respiratory infections. After antibiotic and symptomatic treatment, two bronchoscopies were performed, and both showed stenosis and obturation of the segmental and subsegmental bronchi of the left posterior basal segment, but no foreign body was found. After recanalization and continuous medicamentous treatment, a computed tomography (CT) verified the lung abscess. Video-assisted thoracoscopic surgery (VATS) was performed, and an atypical lung resection was conducted. During the surgery, a foreign body—grass inflorescence from the species Hordeum murinum—was found in the resected tissue. The patient recovered uneventfully after the surgery. Conclusions: Grass inflorescence aspiration in the child population is an extremely rare event, and it represents a diagnostic and therapeutic issue. The exact timing of surgery is very important to reduce complications and avoid death.